2020
DOI: 10.1038/s41598-020-78765-6
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of predator species richness on human hantavirus infection incidence

Abstract: Are predators of rodents beneficial for public health? This question focuses on whether predators regulate the spillover transmission of rodent-borne diseases. No clear answer has emerged because of the complex linkages across multiple trophic levels and the lack of accessible data. Although previous empirical findings have suggested ecological mechanisms, such as resource partitioning, which implies protective effects from predator species richness, epidemiological evidence is needed to bolster these argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Although protective effects could not be confirmed in the present study, these results supported our hypothesis that higher predator species richness could mitigate activity in wild reservoirs ( 40 ), thereby decreasing the risk of spillover. The results of previous studies have suggested significant negative associations with predator species in various rodent-borne diseases ( 41 , 42 ); to our knowledge, the present report is the first to demonstrate a significant association on the basis of HPAI data. This increasing evidence suggests that predatory species diversity has a protective effect, but further confirmatory studies with different diseases in various ecological contexts are needed.…”
Section: Discussionsupporting
confidence: 57%
“…Although protective effects could not be confirmed in the present study, these results supported our hypothesis that higher predator species richness could mitigate activity in wild reservoirs ( 40 ), thereby decreasing the risk of spillover. The results of previous studies have suggested significant negative associations with predator species in various rodent-borne diseases ( 41 , 42 ); to our knowledge, the present report is the first to demonstrate a significant association on the basis of HPAI data. This increasing evidence suggests that predatory species diversity has a protective effect, but further confirmatory studies with different diseases in various ecological contexts are needed.…”
Section: Discussionsupporting
confidence: 57%
“…It has been previously reported that the loss of diversity in ecosystems can increase the risk of Hantavirus transmission due to the loss of the dilution effect [ 48 ]. This dilution effect consists in ecosystems with high diversity where the reservoir-virus-reservoir contact is hindered by their interaction with other organisms [ 42 , 49 , 50 ]. Particularly, in NWA most sites with HPS cases are at a short distance from deforestation areas.…”
Section: Discussionmentioning
confidence: 99%
“…The complementary inverters or circuits generally show the lower energy consumption and the easier integration when compared to the competing routes, while the same rules work well in existing synaptic transistors and circuits. [43,44] Recently, aligned CNT synaptic transistors with self-aligned T-gate structure has facilitated the micrometer-level scaling and the high-speed microsecond-level synaptic activities (Figure 2a), which benefits the future development of large-scale complementary metal-oxide-semiconductor (CMOS)-compatible neuromorphic computing systems. [33] Owing to the sturdiness of the aligned CNT synaptic transistors, a large dynamic range of conductance was effectively tuned by utilizing potentiating and depressing voltage pulses.…”
Section: D Quantum Materials For Artificial Synapsesmentioning
confidence: 99%